Relationship of Nicotine Levels With Prolactant Hormones In Passive Smoking Postpartum Mom - Amrina Amran; Delmi Sulastri; Susilasastri Susilasastri (Journal of Midwifery, 2019)
Absorption of nicotine from the lungs into the blood takes place so quickly that 8 seconds have reached the brain and inhibits the central nervous system. Approximately 85% of housewives in Indonesia exposed to smoke, smokers die 8 for active smokers and passive smokers die because of the exposure to other people's smoke. Cigarette consumption can reduce thevolumeof milk for a right to disrupt thehormone prolactin. The purpose of this study was to determine the relationship between the levels of nicotine in the levels of the hormone prolactin in postpartum mothers smokers pasive . Desain this study was cross-sectional. Thepopulation was postpartum mothers with a total sample of 49 people,by consecutivesampling. Examination of nicotine levels andprolactinhormone levels using the ELISA method. Data were analyzed by univariate and bivariate with correlation test. The results showed that the average nicotine level was 23.18 ± 3.18 ng / ml and the average hormone prolactin level was 7.61 ± 1.72 ng / ml. There is a correlation between nicotine level and prolactin hormone level (r = -0.526), (r 2 = 0.276), (p <0.05). The conclusion of the study is a strong negative correlation between nicotine levels and prolactin hormone levels in passive postpartum mothers.